Modelling the impacts of policy interventions for agrifood systems transformation in Indonesia - Woolfrey, Sean; Bizikova, Livia; Henning, Christian; Boere, Esther; Kozicka, Marta; Laborde, David; Piñeiro, Valeria; Augustynczik, Andrey; Grunenberg, Michael; Havlik, Petr; Illescas, Nelson; Khalifa, Sherin; et al. (Food and Agriculture Organization of the United Nations, 2024)
The Government of Indonesia and FAO have recognized the need for thorough analysis and modelling of Indonesia’s agrifood systems to support agrifood systems transformation efforts in the country. This is needed to provide a better understanding of the governance context in agrifood systems, including the political economy dynamics influencing performance, as well as to identify synergies and trade-offs across different policy goals and optimal policy mixes for achieving multiple policy objectives. In this regard, FAO facilitated a project to pilot an innovative approach to modelling for food systems transformation. This modelling approach was developed and implemented by a team of researchers from IFPRI, IIASA, IISD and Christian-Albrechts- University of Kiel. It uses three different economic models to generate insights that can assist Indonesian policymakers in developing technically sound and politically feasible policy interventions for agrifood systems transformation. This report provides context for agrifood systems transformation in Indonesia and describes the overall modelling approach before synthesizing the results of the individual modelling activities and distilling these into the overall findings of the modelling. It concludes with implications from these findings for policymaking for agrifood systems transformation in Indonesia and suggestions for the next steps. The results of this modelling and the insights drawn from these results are expected to support efforts to translate Indonesia’s commitments on agrifood systems transformation into concrete policy interventions and to inform medium- and long-term development planning by the Indonesian Government.